1990
DOI: 10.1159/000284633
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Borderline from Neurotic Patients

Abstract: The present study tried to separate 30 hospitalized borderline and 30 hospitalized neurotic patients by indicators of deviant thinking. Kolb and Gunderson’s diagnostic interview for borderlines and the Holtzman Inkblot Technique (HIT) were applied as diagnostic instruments. It was possible to separate the two groups by the more severe degrees of deviant thinking with relatively high values for sensitivity and specificity (83 and 93%). If these results can be corroborated in cross-validations with independent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…hysterical or compulsive personality disorder. A relatively high interrater agreement with a blind rater concerning the DIB total score could be demonstrated (r = 0.90) [8]. A more detailed description of the sam ple and the procedures is given in a previous paper [ 8],…”
Section: Methods: Patient Sample Procedures and Instrumentsmentioning
confidence: 91%
See 3 more Smart Citations
“…hysterical or compulsive personality disorder. A relatively high interrater agreement with a blind rater concerning the DIB total score could be demonstrated (r = 0.90) [8]. A more detailed description of the sam ple and the procedures is given in a previous paper [ 8],…”
Section: Methods: Patient Sample Procedures and Instrumentsmentioning
confidence: 91%
“…Having scored the HIT records, the author applied the "Diagnostic Interview for BLs" (DIB) of Gunderson and Kolb [12,13] to the same patients. The German translation of the DIB was used [14], A total score of at least 7 in the DIB was used as a criterion for diagnostic classification: patients with a total score of >: 7 in the DIB were classified as BL, patients scoring below 7 as neurotic [8], In the sample of the 30 neurotic patients the following disorders according to their clinical diagnoses were included: anxiety neuroses (7), neurotic depression (4), obses sive-compulsive neuroses (3), hysteria (4), phobia (3), different types of (neurotic) personality disorders (9), e.g. hysterical or compulsive personality disorder.…”
Section: Methods: Patient Sample Procedures and Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the author thought it was important to discriminate the psychopathology of BPD from hysterical disease by comparative study in our clinical psychiatry in order to treat these patients exactly. Previous findings suggested that not a few neurotic symptoms were admitted in BPD 13,14 . In psychopathology there were some descriptive studies about BPD and hysteria 15–17 .…”
Section: Introductionmentioning
confidence: 99%